EFFECTS OF WEATHER, INCUBATION, AND HUNTING ON GOBBLING ACTIVITY IN WILD TURKEYS - James M. Kienzler; Terry W. Little; Wayne A. Fuller (Wildlife Society Bulletin)
Abstract: The setting of spring wild turkey (Meleagris gallopavo) hunting seasons has been influenced by tradition, gobbling, and hen vulnerability. Knowing the peaks of gobbling and the beginning of incubation is important in setting spring hunting seasons. We were interested in (1) determining the effects of hunting and weather factors on gobbling activity, (2) quantifying daily and seasonal trends in the intensity of gobbling activity, and (3) determining the relationship of chronology of incubation and gobbling activity. Early morning gobbling activity was monitored daily from mid‐March through early June on two areas in south‐central Iowa, 1978‐81. Although no linear trend of gobbling activity and hunter density could be detected (P = 0.87), the presence of hunters depressed gobbling counts (P < 0.001). Temperature and light intensity were also related to gobbling counts (P < 0.01). Precipitation the previous 12 hours and wind were inversely related to the counts (P < 0.01). Although gobbling activity was usually consistent between years, the chronology of nesting did not appear to strictly coincide with gobbling every year. After sunrise, within‐day patterns of gobbling were similar before and during the hunting season. Before the hunting season started, high average counts were relatively higher prior to sunrise, however. Hunting depressed gobbling counts at all times of the day. Hunting was estimated to be responsible for part of the late‐April dip in gobbling activity usually attributed to nesting.